The History of Attribution to Daniel Varuzhan of the Authorship of the Poem “Golden-mother Goddess” by Artashes Harutyunyan - Grigoryan, Seyran (Bulletin of Yerevan University B: Philology, 2024)
The article is devoted to clarifying the authorship of the poem “Golden-mother Goddess” attributed to Daniel Varuzhan. In 1986, it was included in the second volume of the academic three-volume collection of the complete works of Daniel Varuzhan. Since there is no autograph of this poem, the compilers of the scientific publication relied on the collection “Ararat New Songbook”, published in 1946 in Paris. However, literary facts show that the poem “Golden-mother Goddess” belongs to another famous Western Armenian writer - Artashes Harutyunyan, who was also killed during the genocide of the Armenian people in 1915. Artashes Harutyunyan published this poem in 1908 in the Armenian magazine “Eastern Press” and in 1911 in the magazine “Anahit”. By the way, the poem “Golden-mother Goddess” is dedicated to the goddess “Anahit”. In 1912, it was included in Artashes Harutyunyan’s collection “New Lyre”. Due to a textual error, this poem in printed and electronic publications, in literary books, and articles is sometimes presented as the work of D. Varuzhan, and sometimes as the work of A. Harutyunyan. The article explains the possible reasons for the textual confusion. The ideological content and poetics of the poem, its connections with the “pagan movement” of Western Armenian poetry in the early 20th century, are considered. By studying literary analyses devoted to the text of the poem “Golden-mother Goddess”, methodological guidelines for further scientific understanding of this work are considered in the context of the work of its original author, Artashes Harutyunyan. The scientific novelty of the article lies in the fact that it shows the ways of correct publication and research of the attributed poem.